Bacterial community response to changes in a tri‐trophic cascade during a whole‐lake fish manipulation. Issue 3 (March 2016) - Saarenheimo, J.; Aalto, S. L.; Syväranta, J.; Devlin, S. P.; Tiirola, M.; Jones, R. I.
Abstract: Microbial communities play a key role in biogeochemical processes by degrading organic material and recycling nutrients, but can also be important food sources for upper trophic levels. Trophic cascades might modify microbial communities either directly via grazing or indirectly by inducing changes in other biotic or in abiotic factors (e.g., nutrients). We studied the effects of a tri‐trophic cascade on microbial communities during a whole‐lake manipulation in which European perch ( Perca fluviatilis ) were added to a naturally fishless lake divided experimentally into two basins. We measured environmental parameters (oxygen, temperature, and nutrients) and zooplankton biomass and studied the changes in the bacterial community using next generation sequencing of 16S rRNA genes and cell counting. Introduction of fish reduced the biomass of zooplankton, mainly Daphnia, which partly altered the bacterial community composition and affected the bacterial cell abundances. However, the microbial community composition was mainly governed by stratification patterns and associated vertical oxygen concentration. Slowly growing green sulfur bacteria ( Chlorobium ) dominated the anoxic water layers together with bacteria of the candidate division OD1. We conclude that alterations in trophic interactions can affect microbial abundance, but that abiotic factors seem to be more significant controls of microbial community composition in sheltered boreal lakes.